Risk Stratification in Chest Pain: Impact on the Diagnosis of Acute Coronary Syndrome - Reis,Ana Paula Paz (2021)
Abstract Background The implementation of institutional protocols in the emergency department (ED) for risk stratification in patients with chest pain has been recommended. Objective To assess the sensitivity, specificity and predictive value of an institutional risk stratification protocol for chest pain suggestive of acute coronary syndrome (ACS). Method Cross-sectional study conducted based on the computerized records of patients treated with the use of a chest pain protocol adapted from the Manchester protocol. The level of risk was stratified by applying five colors representing the respective levels. Each color represents a level of severity and a maximum waiting time for receiving medical care. Red and orange were considered to be high priority, while patients with yellow, green or blue indications were considered to represent a low priority. To compare the type of diagnosis and the classification of priority for receiving care, the Pearson's chi-square test was used, considering a significance level of p< 0.05 for all tests. Results The records of 1,074 patients admitted to the cardiology ED were analyzed. Men (54%), with a mean age of 60 ± 15 years, with complaints of chest pain (44%) of moderate intensity (80%) were predominant the study. Of these patients, 19% were classified as high priority, while 81% were considered to represent a low priority. ACS was confirmed in 23% of the patients, with 34% of them being classified as high priority and 66% as low priority. The sensitivity of the risk stratification protocol for chest pain was 33.7% and the specificity was 86.0%, with a positive and negative predictive value of 41.7% and 81.3%, respectively. Conclusion The Institutional risk stratification protocol for chest pain suggestive of ACS presented satisfactory specificity and a low degree of sensitivity. Int J Cardiovasc Sci. 2020; [online].ahead print, PP.0-0